Chinese, Japanese and Korean-inspired culinary words in the English language - Kiaer, Jieun; Calway, Niamh; Ahn, Hyejeong (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper discusses how Chinese and Japanese-inspired culinary terms have become part of the English language of food. It investigates the path of culinary terms into popular usage using Google Ngram, and Google Trends. It also takes an in-depth look at social media to discover the impact such technology has on the adoption of Asian culinary terms and further investigates this phenomenon by conducting a survey of 297 L1 and L2 English speakers, mainly from the United Kingdom. By selecting three specific kinds of culinary terms (tea words, dumpling words, and Yoshoku words), this paper showcases the creation of the forms and meanings of these culinary terms and documents their transnational journey to become part of English. The authors argue that the influence of social media, which has little linguistic authority, has made the process of the adoption of new words much more rapid, popularising their use and enabling diversity in their forms more than was ever previously possible.